Pengaruh Independensi, Pengalaman Auditor, Skeptisisme Profesional, Beban Kerja dan Kompetensi Terhadap Kemampuan Auditor Mendeteksi Kecurangan Laporan Keuangan - Vika Frassasti; Novita Weningtyas Respati; Wahyudin Nor (Jurnal Akuntansi dan Keuangan (JAK), 2023)
This purpose of this study is to determine and analyze the direct influence of the dependent variable on the independent variable. Included among the independent variables are independence, auditor experience, professional skepticism, workload, and competency. The dependent variable is the ability of the auditor to identify fraudulent financial statements. The KAP Surabaya auditors serve as the population in this study. Fifty five of the 275 auditors employed by KAP Surabaya constitute the samples in this study. Non-probability sampling is the sampling technique used by researcher. Sampling is conducted by using the method of purposive sampling whichthe criteria of an auditor is a one-year working period. Method of multiple regression analysis is the employed analytical instrument. On the basis of an analysis of the data, it is determined that independence, auditor experience, and a burden have no bearing on the auditor’s ability to detect fraudulent financial statements. In the meantime, professional skepticism and competence enhance an auditor’s ability to detect fraudulent financial statements.